(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
This paper analyzes ambivalent representation of India in William Hodges’ Travels in India. The exploration of politics behind such representation can be interesting area to investigate. The writer has tried to portray the contradiction between ruins, antiquity, and depopulated habitation on the one hand; and modification, cultivation, and populated habitation, on the other. The horrendous act of sati has been depicted in a smart way as Hodges does not criticize Hindu tradition of self-immolation of wives for the death of their husbands; while the same custom was declared illegal and punishable later by English rulers in India during colonial time. Similarly, Hindu art and architecture has not been observed with the spectacle of Greek art which was considered model worldwide; rather it has been depicted as superb and guided by climate, culture, and geography of its own. Promod K. Nayar’s notion of imperial sublime, Saree Makdisi’s Romantic imperialism, and Julie Reiser’s idea on writer as shared nervous system of circumstances have been used to strengthen the argument. The study concludes that the ambivalent representational stances created in Hodges’ narrative try to justify English rule in India in the consolidation phase of the empire. Previous studies highlighted deserted landscape, customs, populations mainly focusing on the representation of Hindus, their art, architecture, the Muslim indolence resulting in devastation and ruin. This study, however, investigated the ambivalent representation and its politics behind the portrayal of the need of English presence in India for modification and habitation. Finally, this study also throws light on the gap for future research on the circumstances that led to the development of negative representation of the natives in colonial writing.